2016
DOI: 10.1097/meg.0000000000000590
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing 10-day sequential, 7-day concomitant and 7-day standard triple therapies for Helicobacter pylori eradication

Abstract: Ten-day sequential therapy was significantly better than 7-day triple therapy in a clinical setting with low rates of clarithromycin and dual resistance. Concomitant therapy was significantly better than standard triple therapy in the subgroup of patients with clarithromycin-resistant strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…When considering only data from studies published in the last 5 years, the cure rate following sequential therapy was still 90-92.6% in 5 Italian studies with more than 1000 patients [26,38-41], and 73% in another study with 100 cases [42]. A similarly high success rate of sequential therapy has been observed in studies recently performed in Slovenia (94.2%) [43], Portugal (90%) [44], Belgium (90%) [3], Israel (95.9%) [45], Thailand (94%) [46], Taiwan (91.9%) [47], Singapore (90.3%) [48], and the United Arab Emirates (88.6%) [49], suggesting that this therapy is still effective in several countries. Based on these findings, Italian, Slovenian, or Portuguese physicians could inopportunely deprive their patients a priori of a still effective therapy by following the European guidelines.…”
Section: Bismuth-free Therapiesmentioning
confidence: 89%
“…When considering only data from studies published in the last 5 years, the cure rate following sequential therapy was still 90-92.6% in 5 Italian studies with more than 1000 patients [26,38-41], and 73% in another study with 100 cases [42]. A similarly high success rate of sequential therapy has been observed in studies recently performed in Slovenia (94.2%) [43], Portugal (90%) [44], Belgium (90%) [3], Israel (95.9%) [45], Thailand (94%) [46], Taiwan (91.9%) [47], Singapore (90.3%) [48], and the United Arab Emirates (88.6%) [49], suggesting that this therapy is still effective in several countries. Based on these findings, Italian, Slovenian, or Portuguese physicians could inopportunely deprive their patients a priori of a still effective therapy by following the European guidelines.…”
Section: Bismuth-free Therapiesmentioning
confidence: 89%
“…A third study from Taiwan also showed an advantage but again failed to show statistical superiority for ST (83.5% vs 77.3%) . Another paper from Slovenia showed more promising results with 94.2% eradication with a 10‐day ST compared to 83.6% for 7‐day standard triple therapy and 91.7% for 7‐day concomitant therapy with the superiority over triple therapy reaching statistical significance …”
Section: Sequential Therapymentioning
confidence: 98%
“…However, higher compliance was achieved with concomitant therapy than with sequential therapy in a meta-analysis of RCTs in Chinese regions [58]. Concomitant therapy is known to demonstrate better eradication rates in patients with clarithromycin- or metronidazole-resistant strains [59, 60], and the selection of secondary antibiotics after first-line concomitant therapy failure remains challenging.…”
Section: First-line Treatment Options For Cases With High Antibiotmentioning
confidence: 99%